Critical issues in environmental taxation - editors Nathalie J Chalifour
The book is clearly structured with the articles divided into Parts and organized by topic. Part 2 features articles on issues relating to the implementation of economic instruments, such as political acceptability, competitiveness, instrument choice and design, institutional issues and even psychological dimensions. Part 3 includes a range of national case studies on topics such as transportation, energy, natural resources and urban sustainability. Part 4 offers a number of papers offering comparative analysis and Part 5 closes with some papers on complementary instruments and alternative approaches